Effect of altitude on 100-m sprint times: an analysis of race times from the finals at major championships - Linthorne, N. P. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to determine the effect of altitude on 100-m sprint times. A nonlinear regression analysis was conducted using competition data from the finals at major championships. The results indicate that the time advantage of competing at an altitude of 2250 m is about 0.19 ± 0.10 s for men and 0.23 ± 0.13 s for women. This is a substantial performance advantage and so the altitude of the competition venue should be taken into consideration when recognizing record performances.